(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article presents clinical and laboratory analytical data on the occurrence of reproductive disorders in adolescent girls. Risk factors for menstrual disorders have been identified. Polymorbidity of the premorbid background was shown, which was more aggravated in patients with the manifestation of disorders in the form of uterine bleeding. The need for a comprehensive differentiated approach to the treatment of patients with menstrual disorders has been established.